Amplificador de tensão com curva de ganho aproximada por partes - Pinheiro, Filipe Maia Lessa (2018)
Automatic Gain Control (AGC) is a system that provides a gain variation of an amplifier from a control signal. This dissertation presents the project of a voltage amplifier with non-linear gain curve using linear piecewise approximation controlled by a AGC system. The gain curve was reconstructed from experimental values. The technique used enabled the implementation of an analog curve by adding the sum of line segments by varying the start points and the angular coefficients. The results obtained from simulations and practical tests showed that the amplifier has the voltage gain as a function of the control voltage following the piecewise approximate. The gain varied between 4 and 0 in a non-linear way controlled by a control voltage variable between 0 and 4 V. The maximum input excursion of the amplifier is 2 VPP and the maximum output excursion of 7.5 VPP